2011
DOI: 10.17796/jcpd.35.3.y052311j23617837
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in Bacterial Loading Using 2% Chlorhexidine Gluconate as an Irrigant in Pulpectomized Primary Teeth: A Preliminary Report

Abstract: Objective: The aim of this study was to evaluate the reduction in bacterial loading using 2% chlorhexidine gluconate as an irrigating solution in pulpectomized primary teeth. Study design: A randomized, controlled clinical trial was performed that included primary teeth with pulp necrosis. Forty necrotic teeth were included, 20 irrigated with 2% chlorhexidine gluconate (experimental group) and 20 with sterile saline solution (control group); in all cases, 2 microbiological samples from within the canals were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 28 publications
0
13
0
2
Order By: Relevance
“…Three studies assessed the efficacy of 2% chlorhexidine gluconate compared with saline solution. Ruiz‐Esparza et al .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies assessed the efficacy of 2% chlorhexidine gluconate compared with saline solution. Ruiz‐Esparza et al .…”
Section: Resultsmentioning
confidence: 99%
“…Three studies 32,33,35 assessed the efficacy of 2% chlorhexidine gluconate compared with saline solution. Ruiz-Esparza et al 32 and Jolly et al 35 both reported a significant decrease, in terms of CFU/mL, in favour of chlorhexidine, whereas Jolly et al 35 reported smaller values than the remaining studies included in the present review. Thus, it was decided not to include their study in the quantitative synthesis.…”
Section: Qualitative Synthesismentioning
confidence: 99%
“…Recent studies have demonstrated that when used in this manner, 2% CG yielded a substantial reduction in deep surgical site infections during both hip and knee arthroplasties [18][19][20][21]. Animal studies have also demonstrated effectiveness of 2% CG solution in eliminating bacteria from Achilles' tendons and in preventing bacterial growth on CG-coated tibial nails implanted in open fractures, though the effective dose and exposure time are not expanded upon in these studies [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…20 this is thus suggested as an alternative for pulpectomy of necrotic primary teeth. 21 though CHX as a root canal irrigant has not shown any long-term damage to host tissues, inflammatory responses were expressed from the host tissues when it was accidently injected beyond the root apex. though CHX is considered as a potent irrigating solution, its ineffectiveness on removal of necrotic remnants and limited action on Gram-negative organisms compared to Gram-positive bacteria it cannot be used as a final irrigant in endodontic cases.…”
Section: Chlorhexidinementioning
confidence: 97%